NLRP3 Inflammasome and Caspase-1/11 Pathway Orchestrate Different Outcomes in the Host Protection Against Trypanosoma cruzi Acute Infection - Paroli, Augusto F.; Gonzalez, Patricia V.; Díaz-Luján, Cintia; Onofrio, Luisina I.; Arocena, Alfredo; Cano, Roxana C.; Carrera-Silva, Eugenio A.; Gea, Susana (Frontiers in Immunology, 2018)
Infection with protozoan parasite Trypanosoma cruzi results in activation of nucleotide-binding domain and leucine-rich repeat containing receptors (NLRs). NLR activation leads to inflammasome formation, the activation of caspase-1, and the subsequent cleavage of IL-1β and IL-18. Considering that inflammasome activation and IL-1β induction by macrophages are key players for an appropriate T cell response, we investigate the relevance of NLR pyrin domain–containing 3 (NLRP3) and caspase-1/11 to elucidate their roles in the induction of different T cell phenotypes and the relationship with parasite load and hepatic inflammation during T. cruzi-Tulahuén strain acute infection. We demonstrated that infected nlrp3-/- and C57BL/6 wild type (WT) mice exhibited similar parasitemia and survival, although the parasite load was higher in the livers of nlrp3-/- mice than in those of WT mice. Increased levels of transaminases and pro-inflammatory cytokines were found in the plasma of WT and nlrp3-/- mice indicating that NLRP3 is dispensable to control the parasitemia but it is required for a better clearance of parasites in the liver. Importantly, we have found that NLRP3 and caspase-1/11 deficient mice differentially modulate T helper (Th1, Th2 and Th17) and cytotoxic T lymphocyte phenotypes. Strikingly, caspase-1/11-/- mice showed the most dramatic reduction in the number of IFN-γ- and IL-17-producing CD4+ and CD8+ T cells associated with higher parasitemia and lower survival. Additionally, caspase-1/11-/- mice demonstrated significantly reduced liver inflammation with the lowest alanine aminotransferase (ALT) levels but the highest hepatic parasitic load. These results unequivocally demonstrate that caspase-1/11 pathway plays an important role in the induction of liver adaptive immunity against this parasite infection as well as in hepatic inflammation.